2020
DOI: 10.1101/2020.04.10.20061192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 most vulnerable Mexican cities lack the public health infrastructure to face the pandemic: a new temporally-explicit model

Abstract: 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…It is projected that the state of healthcare infrastructure in developing countries like South Africa exposes such healthcare systems therein to being easily overwhelmed if an exponential increase in the number of COVID-19 cases is experienced [ 5 , 8 , 9 ]. This understanding and the need to manage the rate of infections across the globe culminated in the lockdown of various economies, thereby resulting in movement restrictions, social distancing, deployment of rapid testing platforms and contact tracing.…”
Section: Introductionmentioning
confidence: 99%
“…It is projected that the state of healthcare infrastructure in developing countries like South Africa exposes such healthcare systems therein to being easily overwhelmed if an exponential increase in the number of COVID-19 cases is experienced [ 5 , 8 , 9 ]. This understanding and the need to manage the rate of infections across the globe culminated in the lockdown of various economies, thereby resulting in movement restrictions, social distancing, deployment of rapid testing platforms and contact tracing.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that social distancing could have a dramatic impact on reducing the number of infected people in Mexico, which is consistent with other studies. A study predicting the vulnerability of fifty Mexican cities found that a 45% adherence to social distancing could reduce the number of infected people by up to 78.7% [43]. While modeled data are useful in planning for health system needs, other countries have begun to measure the true impact of social distancing measures using interrupted time series analyses.…”
Section: Plos Onementioning
confidence: 99%
“…Complaints were particularly mentioned in Nigeria -where the upper class usually goes for medical treatment to HICs [49], but also in Colombia [9], Nepal 9,10 , and even Mexico. 30 The shortage of ICU-beds and of protective clothing was reported in all countries [82,46] but also the construction of provisional treatment units. 8,31 Alternative approaches in South Korea and Kerala/India…”
Section: Vii) Impact On Peoples` Creativity (Survival Strategies)mentioning
confidence: 99%
“…Violent acts of vandalism have been reported, where food trucks were looted (Nigeria [81] and Colombia21 ) or food vendors were attacked by the hungry crowd. An aggravating fact is that in many countries people in the informal sector have no medical insurance (India[30] and Nepal[58]) and cannot receive medical treatment. iii) Impact on migrant workers and refugees Migrant workers or refugees are particularly vulnerable in the containment strategy.…”
mentioning
confidence: 99%